Efficacy of Phlai (Zingiber montanum) Spray Cool Formula in Managing Upper Trapezius Myofascial Pain Syndrome: A Randomized Controlled Trial - Prakairat Tunit; Nurmee Mahama; Nursawiyah Mina; Nasrin Chi; Suwanna Maenpuen; Pornchai Sawangwong; Waratta Hemtong; Phasit Sirited; Chuda Chittasupho (Life)
Phlai (Zingiber montanum) has long been valued for its anti-inflammatory and analgesic properties in traditional medicine. This study aimed to develop and assess the physical stability, chemical composition, and clinical efficacy of a novel Phlai spray cool formula (PSCF) compared to a diclofenac spray (DS) in patients with chronic myofascial pain syndrome. The chemical analysis revealed curcumin (28.73 ± 5.73 mg/100 g), β-sitosterol (50.92 ± 1.27 mg/100 g), and lauric acid (38.86 ± 1.72 g/100 g) as key active compounds. PSCF demonstrated stable physicochemical properties, including pH and peroxide value across storage conditions. In a randomized controlled trial involving 66 participants, PSCF and DS groups exhibited comparable reductions in pain intensity, as measured by the Visual Analog Scale (VAS), from baseline to week 2. Both groups also showed significant improvements in neck disability index (NDI), pressure pain threshold (PPT), and cervical range of motion (CROM). By week 2, the increase in CROM for flexion and extension reached 23.54 ± 4.09° and 19.43 ± 3.20°, respectively, with no significant intergroup differences. The SF-36 health survey indicated notable improvements in overall health status and quality of life, particularly in physical and emotional domains. The analgesic effects of PSCF are attributed to the combined action of menthol, β-sitosterol, and curcumin. The study demonstrated that PSCF offers a therapeutic effect comparable to diclofenac spray without adverse reactions, highlighting its potential as an alternative topical analgesic for chronic myofascial pain management.